The Role of Blockchain Technology in Supply Chain Management - Delviana, Eliza; Fransiska M., Regita; Cantika A., Aline; Alva Endo, Arkam; Addaru T., Kesatuputra (Green Publisher Indonesia, 2024)
In the rapidly evolving digital era, efficiency and transparency are key to gaining a competitive edge in business. Blockchain technology has emerged as a revolutionary solution with the potential to enhance transparency, security, and efficiency in the supply chain. While many large companies have adopted it for various benefits, challenges such as scalability, interoperability, and legal uncertainties still hinder the widespread adoption of blockchain. This research utilizes a literature review to explore the challenges and benefits of implementing blockchain in the supply chain, as well as strategies to enhance data security, transparency, and efficiency. The findings indicate that blockchain can improve transparency, security, and efficiency in the supply chain, but there are still challenges to be addressed. Nonetheless, with proper investment and development, the potential benefits of blockchain in supply chain management (SCM) are significant.